EFEKTIVITAS PEMBELAJARAN VIA WHATSAPP TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PADA MATERI LOGIKA - mitra pasaribu; sri Rahmah Dewi Saragih; Ely Syafitri (Universitas Asahan, 2022)
AbstractThis study ass to describe the effectrvencss of students in solving logic problems ia terms of the mathematical communication skills of students in class X1 of SMA Swadaya in Academic Year 2020 / 2021 . the subjek of the study are 14 student of class X1 of private High School in Academic Year 2020/2021.The instrument in this research are 3 essay questions which refers to indicators of mathematical communication skills. Determination of the sample is done using the total , Sampling technique, Based on the results of data processing, 12 students (85,7%) are belonged to “Hight